2001
DOI: 10.1007/bf02703742
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of drug transport mediated byCaMDR1: A major facilitator ofCandida albicans

Abstract: CaMDR1 encodes a major facilitator superfamily (MFS) protein in Candida albicans whose expression has been linked to azole resistance and which is frequently encountered in this human pathogenic yeast. In this report we have overexpressed CaMdr1p in Sf9 insect cells and demonstrated for the first time that it can mediate methotrexate (MTX) and fluconazole (FLC) transport. MTX appeared to be a better substrate for CaMdr1p among these two tested drugs. Due to severe toxicity of these drugs to insect cells, furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Interestingly, KAE in combination with FLC could synergistically inhibit all the strains after 48 h of incubation in the T-K test (Figure 1) including C. albicans z2003, indicating that it was useful for T-K test to further assess the interpretations acquired in a checkerboard assay when FICI was a little higher than 0.5. The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, KAE in combination with FLC could synergistically inhibit all the strains after 48 h of incubation in the T-K test (Figure 1) including C. albicans z2003, indicating that it was useful for T-K test to further assess the interpretations acquired in a checkerboard assay when FICI was a little higher than 0.5. The upregulations of multidrug efflux pump controlled by Cdr1p, Cdr2p belonging to ATP-binding cassette superfamily (APC transporter) and Mdr1p, a member of major facilitator superfamily (MFS) were implicated in most fluconazole-resistant C. albicans strains (Niimi et al 2004;Holmes et al 2012;Prasad and Rawal 2014) as FLC was a substrate for CDR1, CDR2, and MDR1 (Kohli et al 2001;Nakamura et al 2001). Rhodamine 6G was the most common used fluorescent dye of ABC pump substrate requiring ATP as energy to observe transporter-mediated FLC resistance (Lamping et al 2007;Peralta et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that intracellular [ 3 H]fluconazole levels decreased when CDR1 (20,33) and MDR1 (37) were overexpressed in S. cerevisiae and also that fluconazole MICs increased when CDR1, CDR2 (36,53), and MDR1 (31) were overexpressed in C. albicans. The levels to which CDR1, CDR2, and MDR1 were expressed in C. albicans in the present study did not approach the expression levels that others achieved in S. cerevisiae or C. albicans; this may have been due to our use of episomal rather than integrating vectors and our use of the ACT1 and GAL1 promoters instead of fluconazole-inducible promoters.…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance of the supernatant was measured at 527 nm (23). The passive diffusion of FLC was checked by using radiolabeled [ 3 H]FLC (24,47). The deenergized cells were incubated with 100 nM [ 3 H]FLC (0.7 TBq mmol Ϫ1 ); and aliquots were removed at various times, rapidly filtered, and washed three times with ice-cold buffer A containing an equimolar concentration of cold drug on a Millipore manifold filtration assembly with 0.45-m-pore-size cellulose nitrate filter disks (Millipore, Bedford, Mass.).…”
Section: Methodsmentioning
confidence: 99%
“…The fold increase in resistance to each drug was calculated as the difference in resistance between the nontransformant and transformant pair for each cell type. MTX is the substrate for CaMdr1p (24), and the fold change in resistance is much higher for CaMDR1-transformed erg mutant cells than for CDR1-transformed erg mutant cells. Note the change in the x axis for fold MTX resistance.…”
Section: Fig 6 Graphical Representationsmentioning
confidence: 98%